ANALISIS VISUAL POSTER KIKO PADA SERIAL ANIMASI KIKO MUSIM KE-1 - Risa Adriani (JURNAL Dasarrupa: Desain dan Seni Rupa, 2022)
In the current era, technological progress is growing rapidly. The development of this technology has had an impact on the creative animation industry, judging by the many animated series that have had better quality from time to time. One of them is the animated series made by the nation's children, namely, KIKO. The KIKO animated series is an adaptation of the children's comic series entitled Kiko's Story, which was then redeveloped into an animated series. The role of information and promotion media in making animated serial works is inseparable, namely by designing media posters. In the KIKO animated series, the poster used aims to provide information about the broadcast schedule at one of the television stations. The purpose of this research is to examine the visual elements and find out the meaning contained in the poster. This study uses Kusrianto's visual communication theory and Rustan's visual elements. The method used in this study is a qualitative-descriptive method with the semiotic approach of Kress and Leewuen to analyze the meaning contained in the posters for the KIKO season 1 animated series. This study describes the role of visual elements that provide an overview and meaning according to the content in the KIKO season 1 animated series story.